Análisis del impacto del programa de transferencias monetarias condicionadas Familias en Acción sobre el embarazo adolescente (2017)
This paper analyzes the effect of the Conditional Cash Transfer (CCT) Program Familias en Acción, in its second phase, on teenage childbearing in Colombia. For this purpose, we use the Fuzzy Regression discontinuity design and we instrument by the eligibility in the program which is defined by the SISBEN Poverty index (Information System of Potential Beneficiaries of Social Programs in Colombia). The results suggest that the effects of FA on teenage childbearing depend on the level of exposure to the program. At low levels, participation in the program increases the likelihood of a woman having teenage childbearing. However, as households stay longer in FA, the effect is neutralized until after a certain exposure threshold the effect is reversed. In order to carry out this work, the administrative data of the Monitoring and Evaluation System of Families in Action (SIFA) and the SISBEN census data for 2004-2007 and 2008-2010 are used.